Developing a Digital Da'wah Ecology Model to Enhance the Effectiveness of Da'wah Communication - Cucu Sulastri; Muhamad Yopi (CV Edujavare Publishing, 2026)
The rapid development of digital technology has transformed da’wah practices from conventional approaches into digital-based communication through various social media platforms. This study examines the utilization of digital communication channels in enhancing the effectiveness of da’wah communication at Masjid Jami Al Barokah through the lens of Media Ecology Theory. A qualitative approach with a single case study design was employed. Data were collected through in-depth interviews with mosque administrators, media team members, and congregants, supported by participant observation, social media content analysis, and documentation. The data were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that Masjid Jami Al Barokah utilizes Instagram, Facebook, YouTube, and TikTok to disseminate religious messages and information, thereby expanding audience reach and increasing congregational engagement. However, challenges remain, including limited human resources, the predominance of one-way informational content, and insufficient audience interaction. The study concludes that effective digital da’wah requires the integration of media characteristics, message credibility, and audience participation. Furthermore, it proposes a Digital Da’wah Ecology model that emphasizes the interrelationship between medium, message, and human agency as a foundation for credible, participatory, and adaptive da’wah communication in the digital era.